Unilateral Condylar Hyperplasia of the Mandible - Malachovsky I; Statelova D; Janickova M; Jurkemik J; Adamicova K (Acta Medica Martiniana, 2015)
Condylar hyperplasia (CH) of the mandible is a rare pathology that occurs at the head of the condyle and can lead to facial asymmetry affecting occlusion and possible association with pain and dysfunction. Unilateral condylar hyperplasia is an uncommon condition of unknown aetiology, proper diagnosis of which has to be established, as the patients may look for surgical help. A rare case of unilateral condylar hyperplasia of the mandible is reported here.